PENGARUH PEMBERIAN HEALTH COACHING BERBASIS HEALTH PROMOTION MODEL (NOLA J.PENDER) TERHADAP TINGKAT KECEMASAN IBU HAMIL DI PUSKESMAS DINOYO - Solikhah, Fitriana Kurniasari; Ernawati, Naya (Journal of Nursing Care and Biomoleculer, 2019)
AbstractThe number of pregnant women who experience anxiety tends to increase, things affect the delivery outcome and the physical and mental health of the fetus. Health coaching is the practice of health education and health promotion with a view to improving individual health and to facilitate the achievement of health goals that effectively motivate structured behavior change, through supportive relationships between participants and coaches. The research objective was to analyze the effect of health coaching provision based on health promotion model on the anxiety level of pregnant women. The study design used quasi-experimental, with the number of samples of the treatment and control groups as many as 30 respondents. The study was conducted in the Dinoyo Health Center area of Malang City from October to November 2018, anxiety in the treatment group experienced a significant change with a p value <0.05 using the Wilcoxon test. The conclusion of this study is that the level of anxiety experienced by pregnant women (primigravida and multigravida) is still high. Giving health coaching has a significant effect on reducing anxiety rates in pregnant women.Keywords: pregnant women, health coaching, health promotion, anxiety.  AbstrakJumlah ibu hamil yang mengalami kecemasan cenderung meningkat, hal memengaruhi outcome persalinan serta kesehatan fisik dan mental janin. Health coaching adalah praktik pendidikan kesehatan dan promosi kesehatan dengan maksud untuk meningkatkan kesehatan individu dan untuk memfasilitasi pencapaian tujuan kesehatan yang secara efektif memotivasi perubahan perilaku secara terstruktur, melalui hubungan suportif antara partisipan dan coach. Tujuan penelitian untuk menganalisis pengaruh pemberian health coaching berbasis health promotion model terhadap tingkat kecemasan ibu hamil. Desain penelitian menggunakan quasi eksperimen, dengan jumlah sampel kelompok perlakuan dan control sebanyak 30 responden. Penelitian dilakukan di wilayah Puskesmas Dinoyo Kota Malang pada bulan Oktober sampai November 2018, kecemasan pada kelompok perlakuan mengalami perubahan yang signifikan dengan nilai p<0,05 menggunakan uji wilcoxon. Simpulan penelitian ini adalah tingkat kecemasan yang dialami oleh ibu hamil (primigravida dan multigravida) masih tinggi. Pemberian health coaching berpengaruh secara signifikan menurunkan angka kecemasan pada ibu hamil.